The Effect of Biofertilizer Mixture from Human and Cow Feaces to Physical Parameter of Soil and Water Patin Fish Culture Media in Peat Ponds - Dian Asa Agusta; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurnal Perikanan dan Kelautan, 2020)
This research was conducted in October-December 2019 which took place at Peat Land of Kualu Nenas Village, Tambang District, Kampar Regency, Riau Province and in Soil Laboratory at Agriculture Faculty, Integrated Laboratory, Marine Chemistry Laboratory with Environmental Quality Laboratory at Fisheries and Marine Faculty of Universitas Riau. The objective of this research is to get a best dose of combinations for human and cow faeces biofertilizer to physical parameter of soil and water in media of striped catfish ponds culture. The results of this research indicated that P4 (combinations of human biofertilizer 80% with cow biofertilizer 20%) is a best treatment (peat soil colour 10YR 3/1 brownish black, crude fiber of peat soil 5.43%, bulk density of peat soil 0.15 g/cm3, turbidity of peat water 74.14 NTU, total suspended solid of peat water 49.67 mg/L, absolute weight 17.30 g, absolute length of striped catfish 4.40 cm, and survival rate 86%). The porosity of Peat Soil, the best treatment is in P0 (control). The temperature of peat water that range from 26-29oC is still classified as optimal for aquatic organism.